Henry VIII and the English Reformation - Newcombe, D. G. (David Gordon), 1952- (Lancaster pamphlets., 1995)
When Henry VIII died in 1547 he left a church in England that had broken with Rome - but was it Protestant? This pamphlet provides a clear guide to the main strands of historical thought on the topic, and the political & religious consequences.